TRUK SEBAGAI "MEDIA DAKWAH" ALTERNATIF - asyhari amri (AL-IDZA'AH: Jurnal Dakwah dan Komunikasi, 2022)
Trucks are one of the most popular means of transportation in Indonesia. Trucks operating in Indonesia have a uniqueness that is not found in other countries. The back of the tailgate (generally an open truck) is mostly decorated with typography or paintings that have various themes, but in general the writings contain comedy content, da'wah messages and also words of wisdom. From this phenomenon, this study aims to examine the message of da'wah on paintings and typography contained in trucks. In this case the research will focus on the meaning of typography in trucks. The result is that trucks containing da'wah messages have certain characteristics, including attracting attention, not being patronizing, entertaining, easy to remember, to the point and reaching many areas and audiences. Keywords: Trucks, Messages of Da'wah, Alternative Da'wah.